1979
DOI: 10.1002/j.1552-4604.1979.tb02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Piroxicam Pharmacokinetics in Man: Aspirin and Antacid Interaction Studies

Abstract: Pharmacokinetic studies with piroxicam, a nonsteroidal antiinflammatory agent, have been carried out following the administration of single and multiple oral doses. A plasma half-life of approximately 45 hours is observed, permitting the use of single daily doses in therapy. Enterohepatic recirculation of drug is suggested by the presence of multiple peaks in plasma concentration curves. Piroxicam is highly bound to serum proteins. The absorption and disposition of piroxicam are unaffected by the concomitant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(30 citation statements)
references
References 21 publications
5
25
0
Order By: Relevance
“…The half-life of piroxicam has been found to range between 14.1 and 158.3 h in normal young men (Hobbs & Twomey, 1979). The mean half-life for our group of mainly elderly patients is longer than those described for younger subjects in the This is also observed for other drugs, e.g.…”
Section: Discussionsupporting
confidence: 49%
“…The half-life of piroxicam has been found to range between 14.1 and 158.3 h in normal young men (Hobbs & Twomey, 1979). The mean half-life for our group of mainly elderly patients is longer than those described for younger subjects in the This is also observed for other drugs, e.g.…”
Section: Discussionsupporting
confidence: 49%
“…For most sub jects, however, the level of piroxicam was below the level of detection of the HPLC method (19.2ng/ml). In contrast, the mean steady-state levels of piroxicam after oral dos ing in normal subjects is 4.5 pg ml-1 [10]. The results of the study reported here supports the view that treatment with topical piroxicam gel, as an alternative to oral NSAID therapy, is likely to reduce the incidence of adverse events associated with higher systemic levels of drug after oral dosing.…”
Section: Discussionsupporting
confidence: 65%
“…Concurrent administration of ASA decreased the plasma protein binding of ketoprofen and increased its plasma clearance at steady state (Williams et al, 1981). However the absorption and disposition of piroxicam was apparently unaffected by concomitant administration of ASA (Hobbs & Twomey, 1979). In contrast aspirin has been reported to markedly reduce the bioavailability of diclofenac as measured by AUC (Fowler, 1979).…”
Section: Discussionmentioning
confidence: 99%